Implementation of a Mathematical Modelling of a Rotary Cement Kilns - Serlya Aldina; Juwari Purwo Sutikno; Renanto Handogo (IPTEK The Journal for Technology and Science, 2020)
Rotary cement kiln is the main equipment in the cement industry that has complex dynamic behavior, where any changes will affect the quality of the product and the consumed energy. A one-dimensional model of rotary kiln is needed to understand kiln’s behavior and improve kiln operating and design to achieve the optimum condition of product quality and energy required. In this study, the onedimensional mathematical model of a dry rotary cement kiln with pulverized coal combustion is developed. This model consists of a set of nonlinear ordinary differential equations and nonlinear algebraic equations that describe material and energy balance equations. The model has been solved numerically by using Matlab R2015a, and it has been validated by comparing the result with published experimental data. Based on the result, the steady-state simulation shows that the behavior of the model developed is appropriate with the results presented in the literature. It can be concluded that the model is accurate (error < 6%) to describe the profile of temperature and bed composition along with the kiln. It can be used to obtain a better understanding of kiln’s behavior and improve the kiln operating and design to achieve the optimum condition.